Evaluation of the Weed Infestation, Grain Health, and Productivity Parameters of Two Spelt Wheat Cultivars Depending on Crop Protection Intensification and Seeding Densities - Małgorzata Haliniarz; Dorota Gawęda; Bożena Nowakowicz-Dębek; Agnieszka Najda; Sylwia Chojnacka; Justyna Łukasz; Łukasz Wlazło; Monika Różańska-Boczula (Agriculture, 2020)
Spelt wheat is one of the oldest wheat with very high nutritional value. It does not have particular climatic requirements and tolerates adverse environmental conditions well. The versatile advantages of spelt wheat make it attractive to farmers, plant breeders, food technologists, and consumers. The aim of this study was to determine the effect of different crop protection systems and seeding densities on yield, weed infestation, and grain health of the spelt wheat cultivars “Rokosz” and “Schwabenspelz”. The research showed that the spelt wheat cultivars studied responded differently to production intensification. The use of crop protection chemicals in the crop of the cultivar “Rokosz” resulted in lower weed infestation and in obtaining higher yields. In the case of the cultivar “Schwabenspelz”, production intensification did not have a significant effect on its productivity and quantitative weed infestation parameters. Therefore, this cultivar can be recommended for cultivation in farms with extensive farming methods, for example, in organic farms. In both cultivars studied, an increase in seeding density and chemical plant protection with fungicide caused lower grain contamination with mycotoxins, and the content of individual mycotoxins did not exceed the maximum levels set for grain intended for food and animal feed purposes.